It's AE is "D^4-a^4=0"
"\\therefore\\ the\\ auxiliary\\ equation\\ becomes\\ (D^2 \u2013 a^2 ) (D^2 + a^2 ) = 0\\\\\n\\implies D^2-a^2=0\\ or\\ D^2+a^2=0\\\\\n\\therefore (D \u2013 a) (D + a) (D \u2013 ai) (D + ai) = 0\\\\\n\\therefore D = \\pm a, and\\ D=\\pm ai"
Hence the required solution is
"C.F=[ae^{ax}+be^{-ax}]+[ce^{iax}+de^{-iax}]\\\\\nC.F =[a \\frac{(cosh\\ ax+sinh\\ ax)}{2}]+[b \\frac{(cosh\\ ax-sinh\\ ax)}{2}]+[c \\frac{(cos\\ ax-i\\ sin\\ ax)}{2}+d \\frac{(cos\\ ax-sin\\ ax)}{2}]\\\\\nC.F=[\\frac{a+b}{2}cos\\ ax + \\frac{a-b}{2}sinh\\ ax]+[\\frac{c+d}{2}cos\\ ax + i\\frac{(c-d)}{2}sin\\ ax]"
Where "C_1=\\frac{a+b}{2},\\ C_2=\\frac{a-b}{2},\\ C_3=\\frac{c+d}{2},\\ c_4=\\frac{i(c-d)}{2},\\"
Its solution is
And PI, for "x^4" is;
Putting "D^4=a^4" in "f(D)", then
"PI_1=\\frac10 x^4\\ \\therefore method\\ fails"
Then to find PI, put "D^4+a^4" for "f(D)" and take out "x^4".
"\\therefore PI_1=x^4 \\{\\frac{1}{D^4-a^4+a^4}\\}\\{1\\}\\\\\n\\implies x^4\\ \\frac{1}{D^4}\\{1\\}=x^4\\frac{x^4}{4!} \\implies \\frac{x^8}{4!}-----(ii)"
Also, "PI_2" for "sin\\ bx" is;
Put "D^4=D^2 \\cdot D^2 = (-b^2)(-b^2)"
"\\implies\\frac{1}{(-b^2)(-b^2)-a^4}\\ sin\\ bx = \\frac{1}{b^4-a^4}\\ sin\\ bx ---(iii)"
General Solution is;
"G.S=C.F+PI_1+PI_2 \\implies [C_1\\ cosh\\ ax +C_2\\ sinh\\ ax]+[C_3\\ cos\\ ax +C_4\\ sin\\ ax]+\\frac{x^8}{4!}+\\frac{1}{b^4-a^4}\\ sin\\ bx"
Hence
"G.S=[C_1\\ cosh\\ ax +C_2\\ sinh\\ ax]+[C_3\\ cos\\ ax +C_4\\ sin\\ ax]+\\frac{x^8}{4!}+\\frac{1}{b^4-a^4}\\ sin\\ bx"
Comments
Leave a comment